Politik Hukum Pengelolaan Sumber Daya Air dalam Undang-Undang Sumber Daya Air - Akbareldi, Affan; Candrakirana, Rosita (Peneliti.net, 2024)
The right to water for Indonesian citizens has been regulated in Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia (1945 Constitution of the Republic of Indonesia) which contains written provisions regarding land, water, and the wealth contained therein. Arrangements regarding water resources management policies in Indonesia have undergone several changes. Therefore, it is necessary for us to know about the regulation of water resources management policies that have continued to change to date. The problems that will be examined in this journal are (1) how is the legal politics of water resources management policies from Law Number 10 of 1974 concerning Irrigation to Law Number 17 of 2019 concerning Water Resources; (2) what is the policy model for managing water resources after the enactment of Law Number 11 of 2020 concerning Job Creation. To solve these two problems, the researcher used the doctrinal/normative legal research method through a statutory regulation approach. The research results show that water resources management policies are constantly changing because the State of Indonesia is still looking for an optimal policy model so that all Indonesian people can have water according to their rights.